2019
DOI: 10.1016/j.cognition.2019.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Pupils say more than a thousand words: Pupil size reflects how observed actions are interpreted

Abstract: License: Article 25fa pilot End User Agreement This publication is distributed under the terms of Article 25fa of the Dutch Copyright Act (Auteurswet) with explicit consent by the author. Dutch law entitles the maker of a short scientific work funded either wholly or partially by Dutch public funds to make that work publicly available for no consideration following a reasonable period of time after the work was first published, provided that clear reference is made to the source of the first publication of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
(100 reference statements)
1
4
0
Order By: Relevance
“…For instance, exploring a cooperative motor task, Quesque and Coello 38 reported that the spatial amplification of a grasp-to-place motor action was broader, resulting in a higher arm trajectory, when the partner's eye-level was set at a higher position. This result is in line with the key role of the gaze in the process of action understanding in social contexts [39][40][41][42][43] . Because of their social value, the spatio-temporal variations of object-directed motor actions are also thought to serve as crucial cues for an observer to identify the agent's social goal [44][45][46] .…”
Section: The Combined Effects Of Motor and Social Goals On The Kinemasupporting
confidence: 85%
“…For instance, exploring a cooperative motor task, Quesque and Coello 38 reported that the spatial amplification of a grasp-to-place motor action was broader, resulting in a higher arm trajectory, when the partner's eye-level was set at a higher position. This result is in line with the key role of the gaze in the process of action understanding in social contexts [39][40][41][42][43] . Because of their social value, the spatio-temporal variations of object-directed motor actions are also thought to serve as crucial cues for an observer to identify the agent's social goal [44][45][46] .…”
Section: The Combined Effects Of Motor and Social Goals On The Kinemasupporting
confidence: 85%
“…In addition to reflecting inner states, changes in pupil size appear to have a social signalling function (Quesque et al, 2019 ) and can be considered a form of basic communication between conspecifics (Kret et al, 2014 ). Investigating the social value of changes in pupil size, Hess ( 1975 ) established that women with larger pupils were described by men as “more feminine,” “prettier,” and “softer” compared to women with small pupils (Hess, 1975 ).…”
mentioning
confidence: 99%
“…A number of applications to our findings are conceivable for applications in research and technology, be it in understanding interpersonal communication ( Einhäuser et al., 2010 ; Naber, Stoll, Einhäuser, & Carter, 2013 ; Quesque, Behrens, & Kret, 2019) or in allowing innovative human–computer interfaces ( Strauch, Ehlers, & Huckauf, 2017) .…”
Section: Discussionmentioning
confidence: 88%